Parity and thyroid cancer risk: a meta‐analysis of epidemiological studies. (29th December 2015) - Zhu, Jingjing; Zhu, Xiao; Tu, Chao; Li, Yuan‐Yuan; Qian, Ke‐Qing; Jiang, Cheng; Feng, Tong‐Bao; Li, Changwei; Liu, Guang Jian; Wu, Lang
Abstract: Although observational studies have assessed the relationship between parity and thyroid cancer risk, the findings are inconsistent. To quantitatively assess the association, we conducted a systematic review and meta‐analysis. PubMed and Embase were searched up to January 2015. Prospective or case–control studies that evaluated the association between parity and thyroid cancer risk were included. We used the fixed‐effects model to pool risk estimates. After literature search, 10 prospective studies, 12 case‐control studies and 1 pooled analysis of 14 case‐control studies including 8860 patients were identified. The studies had fair methodological quality. Pooled analysis suggested that there was a significant association between parity and risk of thyroid cancer (RR for parous versus nulliparous: 1.09, 95% CI 1.03‐1.15; I2=33.4%). The positive association persisted in almost all strata of subgroup analyses based on study design, location, study quality, type of controls, and confounder adjustment, although in some strata statistical significance was not detected. By evaluating the number of parity, we identified that both parity number of 2 versus nulliparous and parity number of 3 versus nulliparous demonstrated significant positive associations (RR=1.11, 95% CI 1.01‐1.22; I2=31.1% and RR=1.16, 95% CI 1.01‐1.33; I2=19.6% respectively). The dose‐response analysis suggested neither a non‐linear nor linear relationship between the number of parity and thyroid cancer risk. In conclusion, this meta‐analysis suggests a potential association between parity and risk of thyroid cancer in females. However, the lack of detection of a dose‐response relationship suggests that further studies are needed to better understand the relationship. Abstract : After summarizing evidence from 10 prospective studies, 12 case–control studies and one pooled analysis of 14 case–control studies including 8860 patients, there were significant associations between parity and increased risk of thyroid cancer: parous versus nulliparous, RR1.09, 95% CI 1.031.15; parity number of two versus nulliparous, RR1.11, 95% CI 1.011.22; parity number of three versus nulliparous, RR1.16, 95% CI 1.011.33. On the other hand, the dose–response analysis suggested that there was neither a nonlinear nor linear relationship between the number of parity and thyroid cancer risk.